Consumer Perception And Brand Towards Green Marketing Strategy And Its Impact Through Customer Trust As An Intervening Variable - Frimayasa, Agtovia; Soegeng, Irwin Sukrisno; Mujanah, Siti; Halik, Abdul (Sean Institute, 2025)
This study aims to analyze the impact of green marketing strategy and brand on consumer perception, with customer trust as an intervening variable, specifically for Lee Minerale products. In an era where environmental awareness is increasing, consumers tend to choose products that apply sustainability principles. Green marketing has become one of the key strategies for companies to attract environmentally conscious consumers, but its effectiveness is greatly influenced by the trust built with consumers. This research uses a quantitative approach with Structural Equation Modeling (SEM) and involves a random sample of Lee Minerale consumers. The results indicate that the brand has a significant and strong influence on green marketing and customer trust, making it the most influential variable in the model. This suggests that a strong brand image plays a crucial role in shaping a positive perception of green marketing strategies and in enhancing customer trust. On the other hand, consumer perception did not show a significant effect on either green marketing or customer trust, indicating that individual perceptions of the product are not strong enough to significantly influence green marketing strategies or customer trust. Additionally, customer trust in green marketing approaches significance, but its effect remains weak. This suggests that although customer trust slightly influences perceptions of green marketing, its statistical effect is not strong enough. Overall, these results emphasize the importance of brand strategy in reinforcing perceptions of green marketing and building customer trust. Therefore, companies are advised to focus on improving their brand image to achieve success in green marketing strategies. These findings provide insights for companies looking to optimize green marketing strategies by leveraging brand strength as a key factor.